ANALISIS BUANGAN LIMBAH CAIR DOMESTIK TERHADAP KUALITAS AIR SUNGAI KAHAYAN DAN KESEHATAN MASYARAKAT DI KOTA PALANGKA RAYA - Firmanto, Andris; Gumiri, Sulmin; Elvince, Rosana; Darung, Untung; Sinaga, Soaloon; Kembarawati, Kembarawati (Agrienvi: Jurnal Ilmu Pertanian, 2023)
The management of domestic liquid waste disposal in Palangka Raya City which has not been carried out properly and flowed directly to the drainage has resulted in the flow becoming polluted. The polluted drainage around the Sakan - Mendawai road will have an impact on the water quality of the Kahayan River because it is directly connected to the drainage estuary without prior management. The decline in water quality will of course also have an impact on the quality of the health of the surrounding community who use water from the stream. This research was conducted to determine the quality of domestic wastewater in the drainage flow and how it relates to the water quality of the Kahayan River and the quality of public health around the City of Palangka Raya. The research method was carried out by testing the quality of wastewater and water quality of the Kahayan River. The test parameters consisted of pH, BOD, COD, TSS, Oil-Fat, Ammonia and total Coliform. The test results are compared with the applicable quality standards, and further analysis is carried out. The results showed that the domestic wastewater discharged from the drainage stream could not be channeled directly into the Kahayan River without any management because the BOD, COD, TSS and Ammonia parameters had exceeded the threshold for domestic wastewater quality standards. In terms of public health quality, poor water quality has the potential to become a breeding ground for disease germs that can infect the people who live nearby.